Inkjet printing of multiple layers for large-scale, cadmium-free quantum dot light-emitting diodes - Hübner, Tobias; Brabec, Christoph; Göötz, Britta; Von Malm, Norwin (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Quantum Dot Light Emitting Diodes (QDLEDs) are a promising alternative to the already established organic LEDs (OLEDs) in applications like automotive rear-lights. QDLEDs can exhibit higher luminance characteristics and superior operational stability. In order to be able to transfer the QDLEDs from their research state into market products, the oftenused Cadmium-containing QDs must be replaced by less toxic alternatives. Furthermore, the processing costs for the QDLEDs have to be minimized. We overcome both challenges by utilizing Indium Phosphide based QDs in the devices and applying inkjet-printing as a low-material consumption deposition technique. Inkjet-printing three layers of the stack design on top of each other proofs to be challenging concerning the layers homogeneity both macroscopically as well as microscopically. We present viable approaches for the ink formulation process, substrate-pretreatment steps and printing strategies to overcome wetting, dewetting and coffee-staining issues. The printed layers are investigated via topological and fluorescent tools and the successfully fabricated devices are examined via electrooptical measurements.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Area light source; Indium phosphide quantum dots; Inkjet-printing multiple layers; Quantum dot LEDs